Paediatric pneumococcal disease in Central Europe - Prymula, R; Chlibek, R; Ivaskeviciene, I; Mangarov, A; Mészner, Zs; Perenovska, P; Richter, D; Salman, N; Simurka, P; Tamm, E; Tešović, G; Urbancikova, I; et al. (European journal of clinical microbiology & infectious diseases, 2011)
Streptococcus pneumoniae causes considerable global paediatric morbidity and mortality, despite the availability of safe and effective pneumococcal conjugate vaccines (PCVs). To justify the introduction of PCVs, accurate information on the burden of disease is required. Here, we present an appraisal of the pneumococcal epidemiological situation in 11 Central European countries. The data are based on study findings presented at the 12th Central European Vaccine Advisory Group (CEVAG) meeting, held on 21-22 May 2010 in Sofia, Bulgaria, and a literature review of the PubMed database using the search terms 'pneumococcal' or 'Streptococcus pneumoniae', in combination with 'otitis media', 'pneumonia', 'meningitis' or 'bacteraemia/sepsis', and '[Central European country name]'. The incidence of pneumococcal disease appears to be lower in Central Europe than previously reported for Europe as a whole, with the highest risk in infants aged 0-2 years. The fatality rates in the under fives from invasive infections are up to 40%. A paucity of comprehensive country-specific data on pneumococcal disease burden arises from the lack of homogenous surveillance programmes. Standardised, active surveillance systems are required for the accurate evaluation of the pneumococcal disease burden in the region. Only then can the need for vaccination be addressed.
Keywords: imunizace; Child, Preschool; vakcíny konjugované; otitis media; pneumonie pneumokoková; Otitis Media; Adolescent; Infant; sepse; Child; Europe; dítě; pneumokokové vakcíny; incidence; Pneumococcal Vaccines; mladiství; Sepsis; Meningitis, Pneumococcal; Evropa; předškolní dítě; lidé; Humans; Pneumonia, Pneumococcal; Serotyping; pneumokoková meningitida; kojenec; sérotypizace; Streptococcus pneumoniae; Immunization; Incidence; Vaccines, Conjugate